Segmenting the market for Wavin Plastics - Brennan, Ross, 1957-; Canning, Louise; McDowell, Raymond (London : SAGE Publications Ltd, 2017)
Wavin Plastics is part of Wavin UK, a wholly owned subsidiary of Wavin BV in the Netherlands. The wider Wavin group is one of the biggest manufacturers of plastic pipe systems and other industrial plastics products in the world. This case study is designed to discuss the business strategies which allow it to be eco-friendly and cost-effective.
Originally published in Brennan, R., Canning, L., & McDowell, R. (2014). Segmenting the Market for Wavin Plastics. Business-to-business marketing (3rd ed., pp. 165168). London: SAGE Publications Ltd. Print. ISBN: 9781446273722.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Wavin Plastics; Strategic planning -- Case studies; Business planning -- Case studies; Plastic pipe industry -- Netherlands -- Case studies